Thrombolytic, Membrane stabilizing, Antidiarrhoeal, and Antimicrobial Properties of Bioactive Compounds Isolated from leaves of Sesbania grandiflora Naturally Growing in Bangladesh: Properties of Bioactive Compounds Isolated from leaves of Sesbania grandiflora - Nafisa Binte Arfan; Zubair Khalid Labu; Torikul Islam; Azima Sultana Julie; AK Mohiuddin; Shah Alam Khan (Iranian Journal of Pharmaceutical Sciences, 2016)
Sesbania grandiflora leaves are extensively used locally since ancient time as in traditional systems. Based on mainly folkloric use, we investigated to know the potential of Sesbania grandiflora leaves extracts through biological works in vivo and in vitro. The ethanolic extract of S. grandiflora leaves was partitioned into ethyl acetate soluble fraction (ESF), petroleum ether soluble fraction (PSF), carbon tetrachloride soluble fraction (CTSF), chloroform soluble fraction (CSF), and aqueous soluble fraction (AQSF). The extracts were evaluated for their thrombolytic, membrane stabilizing, antimicrobial and antidiarrhoeal activities and the results were compared with standard drugs; streptokinase for thrombolytic, acetyl salicylic acid for anti-inflammatory, kanamycin for antimicrobial activities and loperamide against diarrhoea. In thrombolytic investigation, among all partitionates, the ESF showed highest % of clot lysis (59.57%) as compared to (69.23%) and (3.07%) exhibited by the standard streptokinase and water. In case of membrane stabilizing study, ESF also significantly inhibited the haemolysis of human erythrocyte membrane both induced by hypotonic solution (64.30 ± 0.64%) and by heat (57.21 ± 0.69%), respectively as compared to (70.12 ± 26%) and (73.90 ± 0.29%) demonstrated by acetyl salicylic acid. In the antidiarrhoeal assay, the ethanolic extract (EE) inhibited the mean number of defecation by 24.97% and 41.05% at 200 mg/kg and 400 mg/kg body weight, respectively. In antibacterial activity, it was exhibited by the extracts being comparatively more prominent on the gram negative bacteria than the gram positive bacteria. Our study revealed that satisfactory amount of flavonoid and tannin presence showed a significant and positive correlation between total phenolic compound contents with pharmacological activities of S. grandiflora.